2016
DOI: 10.1038/ncomms12701
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive imaging of buried electronic interfaces using a decelerated scanning electron beam

Abstract: Recent progress in nanotechnology enables the production of atomically abrupt interfaces in multilayered junctions, allowing for an increase in the number of transistors in a processor. However, uniform electron transport has not yet been achieved across the entire interfacial area in junctions due to the existence of local defects, causing local heating and reduction in transport efficiency. To date, junction uniformity has been predominantly assessed by cross-sectional transmission electron microscopy, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…On the other hand, our recently developed non-destructive imaging method can be performed by controlling the acceleration voltage in scanning electron microscopy (SEM) without modifying a sample and a device [ 2 ]. This method achieves a high in-plane resolution of a few nm without any additional requirements of sample preparation for imaging.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our recently developed non-destructive imaging method can be performed by controlling the acceleration voltage in scanning electron microscopy (SEM) without modifying a sample and a device [ 2 ]. This method achieves a high in-plane resolution of a few nm without any additional requirements of sample preparation for imaging.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding and ultimate improvement of the performance of these devices requires a detailed understanding of physical and chemical process of ion- and electron-transfer occurring at interfaces between phases, e.g., ion insertion kinetics into lithium-ion battery electrodes and electrocatalysis at fuel-cell electrodes. For interfaces between two solids, e.g., the electrode/electrolyte interface in an all-solid-state battery, or the electrode/electrocatalyst/membrane interface in a fuel cell, there are only few methods of characterization available, such as transmission electron microscopy (TEM), X-ray computed tomography, and neutron reflectometry. Moreover, these methods typically require a costly and potentially damaging or perturbative high-energy radiation source and do not directly report the electrochemical activity but infer it from other properties . Structural deformation and compositional variation, which affect ions dynamics and kinetics of the entire device occur at nanoscale length scales, requiring an in situ characterization technique to provide this resolution.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have demonstrated chemical analysis alongside decelerated electron-beam imaging for buried magnetic tunnel junctions (MTJs) to reveal the origin of the reduction in tunnelling magnetoresistance (TMR) ratios for some of the MTJs. We have recently developed a new non-destructive method to image buried junctions using a decelerated electron-beam 5 . By using a precisely controlled beam we have managed to image MTJs below an 80-nm-thick Au electrode, allowing a correlation between the junction images and their magnetic transport properties to be made.…”
Section: Introductionmentioning
confidence: 99%